A study on customer care center and complaints handling of Kontena Nasional Berhad / Azizah Ahmad Johan - Ahmad Johan, Azizah (Faculty of Business and Management, 2010)
This case study exploring the Customer Care Center and Complaint handling by Kontena Nansional Berhad. Here, there are some issues in this study that have been analyze the factors that contribute in this issues and discussing some sort of ideas of what Kontena Nasional should be taken in order to improve their Customer Service Center especially in complaint handling. In order to justify on what are the organization implement in providing the product and attracting the customer, the observation has done for 20 weeks. Through this observation, there are some of issues that related to the customer care benefits, complaints handling process base on ISO 10002:2004. On the other words, this study on this issues want to show, what customer care center done, in fact, cover a very wide range of absolutely essential business activities that bring to the customer the product that they want, where, when and with all the information that they need to make informed and satisfying customer’s choices. All of these issues deeply explained in the report in order to be more clarifying for understanding the importance of complaints handling in effective way. Therefore, there are some of suggestions that have been explained in enhancing the sales target.